ANALISIS KELAYAKAN INVESTASI PENAMBAHAN SETORAN MODAL PEMERINTAH KOTA XYZ PADA PT BANK LAMPUNG - Neny Desriani; Pigo Nauli (Faculty of Economics and Business, 2019)
This study aims to measure the value of investment is ideal amount and feasible to invest by Government City XYZ to PT Bank Lampung. The methods used in this study is ratio analysis and investment faeasibility analysis (Payback Period, Net Present Value, Internal Rate of Return, Profitability Index). The result of this study indicate that investment the results of this study indicate that the investment made by the XYZ city government was feasible in a certain amount.